حدِّ حرابہ اور اس کے نفاذ سے متعلق فقہی اختلافات کا تقابلی جائزہ - Mushtaq Ahmad; Muhammad Zakariya; Atta ur Rehman (Pakistan Journal of Islamic Research)
The term Hirāba which was later on placed in the category Ḥudūd (Specified Punishment for certain crimes discussed in Qurʼān or Sunnah) preceded by 33rd verse of Surah al-Maida where death or crucifixion or cutting of a hand and a foot from alternate sides or banishment has been laid as punishment for those who are found waging war against Allah and his Messenger and causing disruption on the earth. Here controversies among the jurists have been penetrated about the site of commission, modus operindi and the question of the power and jurisdiction of the court with reference to the enforcement of the mentioned punishments raised after the separate interpretations made by jurists. Crucifixion in the form of open-hanging was termed as fanatic and barbaric sort of execution and hence was not accommodated in Ḥudūd Ordinance 1979, but current circumstances and severe forms of anti-state raids, kidnaping teenagers, their assassination after committing rape and alike has led the contemporary thought to the Parliament for the revival of crucifixion in the form of open hanging. The enforcement of the latest punishment of Nafi (banishment) is also a controversial juristic matter whether to replace it by due imprisonment or it should be enforced as per Qurʼānic injunctions. All such controversies and differences of the juristic opinion and interpretation have been tried to be explored and analyzed in this short article with a conclusion that Ḥudūd-e-Sharīáh are still mod and can ensure a stable state and a peaceful society.